Quantification of the Carbon and Biomass Content of a Remaining Forest of Polylepis Spp. In the Peruvian Andes. - Cordova Cordova, O.R (2024)
The objective of this research was to quantify the contents of aboveground biomass and carbon of Polylepis spp. “queñoa”, in a relict forest of the Muylaque countryside community in the department of Moquegua between 3,700 and 4,300 m.a.s.l. Under a forest inventory, dasometric parameters (stem diameter, crown diameter, total tree height) were recorded in 20 × 20 m plots, following MINAM (Peruvian Ministry of the Environment) guidelines, to then calculate biomass through the application of an allometric equation for Polylepis and the conversion factor obtained from samples of 20 individuals with the photometric method to find the stored carbon. The laboratory results showed that the conversion factor from biomass to stored carbon was 0.58. In addition, using the information per plot in the forest inventory and applying the allometric equation, the expansion factor per hectare and the conversion factor from biomass to carbon, the following values were estimated: carbon content stored in ton per hectare (1.388 ± 0.5965 tC /ha) and aerial tree biomass in tons per hectare (and 2,394 ± 1,028 tB/ha). The forest of Polylepis spp. studied is considered in the storage of aerial tree biomass and carbon as low compared to most other forests in humid tropical zones and forest plantations with exotic species, however, a higher carbon content can be found in wood due to its density. Therefore, the importance of its conservation to provide habitat for species and environmental services for people makes it a priority to obtain basic information. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.